Analysis of the Level of Abrasion on the Coast of Bukit Batu Sub-District, Bengkalis Regency, Riau - Paramita, Elisa; Rifardi, Rifardi; Feliatra, Feliatra (Fakultas Perikanan dan Kelautan Universitas Riau, 2022)
The purpose of this study is to determine the rate of shoreline change and the level of abrasion in Bukit Batu District, Bengkalis Regency, Riau Province based on several physical variables in the coastal area. End Point Rate (EPR) is a method that can be used to calculate the rate of shoreline change by displaying transects according to their category (high abrasion, medium abrasion, low abrasion, stable, and accretion). From 1991-2021 there was an abrasion of ±139.71 m equivalent to ±4.65 m/year which mostly occurred in Sukajadi Village and Pangkalan Jambi Village, while accretion of ±27.51 m equivalent to ±1.58 m/year mostly occurred in Pakning Asal Village and Sejangat Village. Moderate abrasion is the predominant type. Sukajadi and Pangkalan Jambi are villages that have experienced high levels of abrasion. The area affected by abrasion has moderate and fast currents as well as coastal protection in the form of mangroves, most of which have been damaged and require repairs. Therefore, the main factors causing the abrasion are thought to be the lack of coastal protection and high-speed currents and waves flowing from the Malacca Strait.